Synthesis and properties of starch-g-poly(maleic anhydride-co-vinyl acetate) (eXPRESS Polymer Letters)
Starch-g-poly(maleic anhydride-co-vinyl acetate) (SMV) was synthesized via the esterification reaction of starch with the copolymer of maleic anhydride and vinyl acetate. The carboxylic unit percentage (CUP) of SMV was tailored with reaction conditions, and it ranged from 29.8 to 46.9%. The structure and the morphology of the copolymers were characterized with Fourier Transform Infrared spectroscopy and X-ray diffraction analysis. It was found that SMV could form complex with some metal cations such as Ca2+, Pb2+ and Hg2+ or cationic polyelectrolyte chitosan, and precipitate from the solution. The weight of precipitation increases with an increase of the CUP of SMV. In addition, a physically cross-linked hydrogel of SMV/poly(vinyl alcohol) (PVA) was obtained by freeze/thaw technique. Scanning electron microscopy exhibited the hydrogel was uniform. The gel exhibited pH-responsive re-swelling. The maximum swelling-ratio values of SMV/PVA (9:1, wt/wt) gel were 3.29 and 5.34 in HCl (pH 1.0) and phosphate-buffer saline (PBS) (pH 12) respectively.